Community Service Mentoring UKM Muda Karya Towards Nationally Competitive SMEs Based on Digital - Usman, Halim; Mustafa, Sri Wahyuny; Sukri, Sukri; Riyanti, Riyanti; Rosdiana, Siti (Entrepreneurship Undergraduate Program at Amkop Business School, 2024)
MSME development requires a holistic and ecosystem-based approach, covering at least 6 aspects: policy, financial access, market, human resource capacity, mentoring and culture. Digitalization plays an important role in combining these six components and further accelerating MSME development programs. Organic farming is now starting to be widely known in the community along with a healthy lifestyle. Many organic farming actors have emerged along with the increasingly open market share. UKM Muda Karya is one of the UKM in Palopo City that produces Bokasi Compost Fertilizer and intends to become a DIGITAL-BASED UKM, but the UKM still has several problems in realizing this desire. The purpose of this activity is to 1) resolve the problems faced by UKM Muda Karya Partners, 2) Implement the Merdeka Belajar Kampus Merdeka program, 3) increase the number of digital-based MSMEs.Keywords: Digitalization, SMEs, MBKM, Kaizen, Muda Karya